2018
DOI: 10.1002/jum.14661
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Real‐time Ultrasound Imaging for the Assessment of Trunk Stabilizer Muscles: A Systematic Review of the Literature

Abstract: Rehabilitative ultrasound (US) imaging is one of the popular methods for investigating muscle morphologic characteristics and dimensions in recent years. The reliability of this method has been investigated in different studies. As studies have been performed with different designs and quality, reported values of rehabilitative US have a wide range. The objective of this study was to systematically review the literature conducted on the reliability of rehabilitative US imaging for the assessment of deep abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…In this study, the muscle thickness changes were measured with a Madison X8 ultrasound machine (made in Korea) with a linear probe (with a frequency of 7.5-10.5 MHz). The reliability of this method was previously reported [16]. Before performing the exercises, the location of selected muscles was specified by a radiologist at resting position on the dominant side (preferable leg for hitting the ball for at least two times of three attempts).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the muscle thickness changes were measured with a Madison X8 ultrasound machine (made in Korea) with a linear probe (with a frequency of 7.5-10.5 MHz). The reliability of this method was previously reported [16]. Before performing the exercises, the location of selected muscles was specified by a radiologist at resting position on the dominant side (preferable leg for hitting the ball for at least two times of three attempts).…”
Section: Methodsmentioning
confidence: 99%
“…Using ultrasonography allows the investigation of the deep tissues and internal organs, such as muscles, tendons, ligaments, bursas, and joints. In this method, the cross-sectional area and linear dimensions of muscles are measurable and have many applications in musculoskeletal evaluation [16].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Ultrasound is a highly reliable equipment used to assess whether the muscles are contracting well [14]. Also, it is non-invasive, easy to apply, economical, and can visualize the contraction of the core muscles to provide an immediate visual feedback effect [15].…”
Section: Original Articlementioning
confidence: 99%
“…2.0 (Prim Fisioterapia y Rehabilitación, Madrid, Spain) ( Figure 1)-is an evolution of this first model [16], and was developed to redirect pressure, and based on abdominal-perineal synergy and the expiratory function of the TrA, an adjustable increase in expiratory flow may be generated [17]. Rehabilitative ultrasound imaging (RUSI), commonly used for the study of muscle morphology and characteristics, has been shown as a technique which presents good reliability with regard to trunk stabilizers [18]. The validity of ultrasound measurements of this musculature has been compared with measurements using magnetic resonance imaging (MRI), obtaining an intercorrelation coefficient (ICC) between 0.78 and 0.95 [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, RUSI was used to compare lateral abdominal musculature thickness using ADIM versus a forced expiration through the EFCD with the purpose of evaluate the effects on the core muscles of a directed and regulated expiration by an EFCD device with respect to the ADIM. Rehabilitative ultrasound imaging (RUSI), commonly used for the study of muscle morphology and characteristics, has been shown as a technique which presents good reliability with regard to trunk stabilizers [18]. The validity of ultrasound measurements of this musculature has been compared with measurements using magnetic resonance imaging (MRI), obtaining an intercorrelation coefficient (ICC) between 0.78 and 0.95 [3].…”
Section: Introductionmentioning
confidence: 99%